PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA SALIBABU KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - HUMAPI, JULIEN; Ogotan, Martha; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2017)
The purpose of this studi is to understand how the role of community empowerment institutions(LPM) in the village of Salibabu District Salibabu Talaud Island.The research used qualitative method. 10 respondents from Salibabu Village Head, Section Headof Village Development og Salibabu Village, Chairman and one Board member/member of BPD, Chairmanand one LPM management, And two members of the village community. Data collection with interviewtechnique; While data analysis using qualitative analysis technique of interactive model from Miles andHubernann.Based on the results of research drawn conclusions: (1) LPM does not play an active role indevelopment planning in the village. LPM is not actively participating in village planning (musrembang)planning meetings to develop and establish a Medium Term Development Plan for Villages and AnnualDevelopment Plans or so-called Village Government Work Plans (RKPD). (2) LPM has little active role inthe implementation of village development. LPM is not actively involved in the implementation of villagedevelopment programs. (3) LPM has little role as a forum for participation of villagers in villagedevelopment. LPM is not actively accommodating, channeling and fighting for the aspirations on the villagecommunity in rural development, and not actively ancouraging and mobilizing the participation and selfhelpof the village community.Based on the conclusions of the research results, suggestions can be put forward: (1) LPM shouldcontinue to be encouraged to participate actively in assisting village government in village developmentplanning and implementation. Therefore, LPM must be given allowances or incentives. (2) LPM shouldcontinue to be encouraged to take an active role in the implementation activities of village developmentprograms, by providing operational costs. (3) LPM should continue to be empowered to take and active roleas a container for aspirate suppliers, and mobilize community participation in village development. For that,LPM should be given a proportional role in the deliberations of village development planning and decisionmakingof village development programs.Keywords: Role of LPM, Rural Development